Building a custom large-scale panel of novel microhaplotypes for forensic identification using MiSeq and Ion S5 massively parallel sequencing systems. (March 2020) - de la Puente, M.; Phillips, C.; Xavier, C.; Amigo, J.; Carracedo, A.; Parson, W.; Lareu, M.V.
Graphical abstract: Highlights: 107 autosomal and 11 X chromosome novel, highly polymorphic microhaplotypes compiled. A single FFPE Ampliseq panel validated on Ion S5 and MiSeq MPS platforms. 5 MHs excluded as a result of MPS sequencing performance evaluations. Very high sensitivity to low-level and degraded DNA which typifies forensic samples. The panel of 113 MHs offers straightforward mixture detection - mixture deconvolution feasible. Abstract: A large number of new microhaplotype loci were identified in the human genome by applying a directed search with selection criteria emphasizing short haplotype length (<120 nucleotides) and maximum levels of polymorphism in the composite SNPs. From these searches, 107 autosomal microhaplotypes and 11 X chromosome microhaplotypes were selected, with well-spaced autosomal positions to ensure their independence in relationship tests. The 118 microhaplotypes were assembled into a single multiplex assay for the analysis of forensic DNA with massively parallel sequencing (MPS). A single AmpliSeq-adapted primer set was made for Illumina MiSeq and Thermo Fisher Ion S5 MPS platforms and the performance of the assay was comprehensively evaluated in both systems. Five microhaplotypes showed critical sequencing failures in both MPS platforms and were removed, while a further 13 required manual checks and the application of sequence quality thresholds in one or both systems to ensure the successful analysis of low-level DNA in these loci. The targeting of short microhaplotype spans during marker selection, with an average length of 51 nucleotides in the 118 loci, led to a high level of sensitivity for the panel when sequencing the very degraded DNA typically encountered in forensic casework and the identification of missing persons.